Simulation Study on Power Factor Correction Controlling Excitation Current of Synchronous Motor with Fuzzy Logic Controller - GANÄ°, Ahmet; KEÃECÄ°OÄLU, ÃkkeÅ Fatih; AÃIKGÃZ, Hakan; YILDIZ, Ceyhun; ÅEKKELÄ°, Mustafa (International Journal of Intelligent Systems and Applications in Engineering, 2016)
The correction of power factor in electric power systems is called reactive power compensation. A synchronous motor is used as a capacitive reactive power generator in compensation systems. It is less costly for an enterprise to use a synchronous motor as both mechanical power generator and power factor corrector, which increases their efficiency. There are various studies on increasing the efficiency, capacity and stability of a power system using power factor correction under different operating conditions. This study focuses on the power factor correction of the system by controlling the excitation current of the synchronous motor via fuzzy logic thanks to the asynchronous motor connected to the system.